ANALISIS KESALAHAN BERBAHASA TERHADAP BERITA TERKINI DI MEDIA CETAK SURAT KABAR - Br Sembiring, Miranda Elisa (Cahaya Ilmu Bangsa Institute, 2025)
The aims of this research are (1) to describe language errors in terms of spelling, morphology, syntax and semantics contained in the Sinar Indonesia Baru newspaper; (2) to provide corrections to language errors in terms of spelling, morphology, syntax and semantics contained in the Medan Pos General Daily letter with the title Even though the money is 20% of the APBN. This research is descriptive qualitative research. The data collection technique used is a listening technique to obtain data by listening to the use of language and a note-taking technique to record words or sentences for analysis. The results of the analysis regarding the analysis of language errors in the Medan Pos General Daily letter with the title Even though the money is 20% of the APBN, it can be concluded that there are forms of language errors in the areas of spelling, morphology, syntax and semantics. Keywords: Spelling, Semantics, Syntax, Morphology